Combined alverine citrate and simeticonein preparation in the treatment of irritable bowel syndrome - Ye. A. Poluektova; S. Yu. Kuchumova; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2012)
Aim of investigation. To assess the effect of combined drug meteospasmyl on intensity of clinical symptoms of irritable bowel syndrome (IBS).Material and methods. Retrospective analysis of efficacy and safety of meteospasmyl in 30 patients with IBS diagnosis, confirmed by conformity of complaints to Rome-III criteria and absence of pathological changes at laboratory and instrumental investigations was carried out. Thirteen patients had clinical pattern of diarrhea predominance (IBS-D), 17 – predominance of constipation (IBS-С). The group IBS-D included 7 men (53,8%) and 6 women (46,2) with mean age of 39,2±3,0 years. The group IBS-С included 9 men (52,9 %) and 8 women (47,1%), mean age was 39,7±3,0 years. Meteospasmyl was prescribed in a dose of 1 capsule tid before meal for 28 days. Intensity of IBS symptoms as well as presence of side effects was estimated on 7, 14, 21 and 28-th day of treatment by 4-mark scale of symptoms degree, visual analog scales (VAS), verbal and nonverbal pain rating scale (PRS).Results. In IBS-D group of the patients, after 4-week course of meteospasmyl treatment stool frequency significantly decreased, consistency of feces became less loose. Intensity of abdominal pain by VAS data significantly decreased at the end of 4-week treatment course. Besides that, the drug appeared more effective in relieving symptoms of functional dyspepsia, such as nausea, belching and early satiety. Similar data have been obtained in IBS-С group. To the end of 4-week meteospasmyl treatment course remission has been achieved in 10 of 17 patients in IBS-D group (58,8%) and in 8 of 13 in group IBS-С (61,5%). According to analysis of patients’ diaries, examinations at physician’s visits no adverse effects in the majority of investigated patients has been marked, that confirmed good tolerability of meteospasmyl in all patients.Conclusions. The 4-week course of treatment by meteospasmyl significantly reduces severity of basic symptoms of IBS (abdominal pain, disorder of frequency and consistence of stool, meteorism). Moreover, the drug is effective for relief of symptoms of functional dyspepsia, concomitant to IBS, such as belching, nausea and early satiety. Its good tolerability in all investigated patients was revealed.